2022
DOI: 10.1039/d2bm00359g
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid-based polymeric micelles to ameliorate amyloidogenic disorders

Abstract: To develop anti-amyloidogenic inhibitors for ameliorating the treatment of diabetes, herein, we have synthesized amphiphilic block copolymers with side-chain fatty acid (FA) moieties via reversible addition fragmentation chain-transfer (RAFT) polymerization....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…Further to detect the growth and morphologies of insulin fibrillar aggregates in the absence and presence of polymers, transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were employed. [ 51 ] In the absence of polymers, a densely populated and extensively long robust fibrils were observed in TEM images ( Figure 3 A). However, the number of fibrils diminished remarkably in the presence of polymers and a few very short fragmented fibrils were spotted.…”
Section: Resultsmentioning
confidence: 99%
“…Further to detect the growth and morphologies of insulin fibrillar aggregates in the absence and presence of polymers, transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were employed. [ 51 ] In the absence of polymers, a densely populated and extensively long robust fibrils were observed in TEM images ( Figure 3 A). However, the number of fibrils diminished remarkably in the presence of polymers and a few very short fragmented fibrils were spotted.…”
Section: Resultsmentioning
confidence: 99%
“…Many observations indicated that the interaction of sugar with proteins is very weak, and this interaction can be improved by a multivalent effect; thus various polymeric compounds have been reported such as glycopeptides, 33 glycoden-drimers, 34 and glycopolymers. 35 We previously reported polymeric systems with amino acid, 36 cholic acid, 37 and fatty acid 38 side chain pendants, and studied their interaction with the protein oligomers or preformed fibrils to inhibit matured fibril formation. Various interactions such as electrostatic and hydrophobic interactions and hydrogen bonding played important roles towards the inhibition process of insulin amyloid formation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, formation of insulin fibrils is a foremost concern during the manufacture of insulin, for long-term storing purposes, and for long-distance shipping of the protein, and any degree of formation of amyloid aggregations results in a reduced efficacy of insulin administration. 5 As a preventive measure, various types of therapeutic agents such as surfactants, chemical osmolytes, 6 chaperones, 7 polyphenols, 8 small peptides, 9 nanoparticles (NPs), 10 antioxidant polymers, 11 polymeric micelles, 12,13 several drugs, 14 enzyme inhibitors, 15 and gene therapy method 16 have been reported to prevent the formation of amyloid aggregates. Even though a large number of antiamyloidogenic agents have been designed for averting the protein fibrillation pathway, the major concern in these current remedies is the lower stability of the compounds in the biological system and the poor permeability through the blood−brain barrier (BBB).…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a preventive measure, various types of therapeutic agents such as surfactants, chemical osmolytes, chaperones, polyphenols, small peptides, nanoparticles (NPs), antioxidant polymers, polymeric micelles, , several drugs, enzyme inhibitors, and gene therapy method have been reported to prevent the formation of amyloid aggregates. Even though a large number of antiamyloidogenic agents have been designed for averting the protein fibrillation pathway, the major concern in these current remedies is the lower stability of the compounds in the biological system and the poor permeability through the blood–brain barrier (BBB).…”
Section: Introductionmentioning
confidence: 99%